The The Effectiveness of Used Video And Poster On Increasing Public Knowledge About Covid-19 Prevention Health Protocol - Atik, Atik Farokah; Intan, Intan Nur Amira; Eryantika, Eryantika Cipta Dewi (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
One of the efforts made by the government in preventing the spread of Covid is educating the public about health protocols. However, the implementation of health protocols in the village isn’t optimal. There is need an educational efforts for rural communities. One of the media that can be used to educate the village community is use video and poster media. This research is a quasi-experimental study with a two group pretest-posttest design. The population is the community in Kwadungan Village, Ngasem District, Kediri Regency. The sampling technique used Non Probability Sampling with purposive sampling technique. Techniques Data analysis used statistical t-test in each group. Data analysis was processed with SPSS. The results of the analysis obtained the average level of knowledge of the video group with a pretest score percentage of 21.5% and a posttest score percentage of 28.5%. While the results in the poster group the pretest score percentage of 29.2% and the posttest score percentage of 30.8%. The average educational effort through video is 2.62 while on poster media is 1.93. These results is counseling using video media provides more effective results than counseling using poster media Keywords: Covid-19, Poster, Video, educational media